Cancer predisposition syndromes in children - D. Yu. Kachanov; R. T. Abdullaev; T. V. Shamanskaya; Ye. V. Inyushkina; K. V. Dobrenkov; R. F. Savkova; S. R. Varfolomeeva (Онкогематология, 2022)
The aim of the study was to assess the prevalence of cancer predisposition syndromes among children with cancer in Moscow Region (MR).   The data on patients were retrieved from the database of Childhood Population-based Cancer Registry of MR. 35 (3.0 %) children with cancer predisposition syndromes were revealed among 1173 registered from 2000 till February 2010. The most prevalent syndromes were hereditary retinoblastoma (RB) – 9 (25.7 %), Down syndrome – 8 (22.8 %) and neurofibromatosis type 1–8 (22.8 %). Genetic syndromes were observed in patients with retinoblastoma – 31 %, germ-cell tumors – 6.8 % and soft tissue sarcomas (STS) – 4.5 %. The increased risk of development of leukemia in patients with Down syndrome was observed. The relative risk (RR) of 15.0 (95 % CI 1.9–333.1) for leukemia and 57.1 (95 % CI 9.3–1398.0) for AML was observed. The association of neurofibromatosis type 1 with the development of tumors of central nervous system and soft tissue sarcomas was proved. The RR was 62.5 (95 % CI 8.1–1388.6) for CNS tumors and 150,0 (95 % CI 26.9–3480.9) for STS.